2016
DOI: 10.1002/art.39602
|View full text |Cite
|
Sign up to set email alerts
|

Histone Demethylation and Toll‐like Receptor 8–Dependent Cross‐Talk in Monocytes Promotes Transdifferentiation of Fibroblasts in Systemic Sclerosis Via Fra‐2

Abstract: Objective To investigate whether epigenetic changes can modulate monocytes to produce tissue inhibitor of metalloproteinases 1 (TIMP‐1) via Fra‐2 (an activator protein 1 [AP‐1] family member), a novel downstream mediator that promotes fibrogenesis. Methods AP‐1 transcription factors and TIMP‐1 expression were measured in monocytes from systemic sclerosis (SSc) patients and healthy controls. Involvement of Fra‐2 in the regulation of TIMP‐1 following treatment with Toll‐like receptor 8 (TLR‐8) agonist was invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 31 publications
(45 reference statements)
0
32
0
Order By: Relevance
“…Apicidin is another histone modifier inducing histones hyperacetylation. We have previously validated that DZNep and apicidin concentrations, which were used to stimulate monocytes, did not affect cells viability . This suggests that only specific epigenetic agent (DZNep, but not apicidin) plus TLR8 stimulation can activate monocytes to produce profibrotic genes and changes cell morphology.…”
Section: Resultsmentioning
confidence: 92%
“…Apicidin is another histone modifier inducing histones hyperacetylation. We have previously validated that DZNep and apicidin concentrations, which were used to stimulate monocytes, did not affect cells viability . This suggests that only specific epigenetic agent (DZNep, but not apicidin) plus TLR8 stimulation can activate monocytes to produce profibrotic genes and changes cell morphology.…”
Section: Resultsmentioning
confidence: 92%
“…Interestingly, single stranded RNA is found in many types of virus, suggesting that a viral origin is responsible. We have now demonstrated that the single stranded RNA mediates TIMP-1 via TLR8 and depends on trimethylation of histone27 which alters the expression of the AP-1 transcription factor Fos-Related Antigen-2 (FRA2) [58]. This links possibly viral activation of TLR8 to activation of FRA2 via epigenetic modulation by histone methylation [58].…”
Section: Internal Tlrsmentioning
confidence: 99%
“…It has also recently been found that the AP-1 family member, Fos-related antigen 2 (Fra2), facilitates TLR8-mediated overexpression of TIMP-1, in ex vivo monocytes derived from patients with SSc 45. Skin-infiltrating monocytes from patients with SSc showed an increase in Fra2; treatment of these monocytes with a histone demethylation agent caused an increase in both Fra2 and TIMP-1 production when challenged with the TLR8 agonist ssRNA; and increased TIMP-1 can directly induce myofibroblast transdifferentiation 45.…”
Section: Tlrs In Sscmentioning
confidence: 99%
“…Skin-infiltrating monocytes from patients with SSc showed an increase in Fra2; treatment of these monocytes with a histone demethylation agent caused an increase in both Fra2 and TIMP-1 production when challenged with the TLR8 agonist ssRNA; and increased TIMP-1 can directly induce myofibroblast transdifferentiation 45. The factors affecting transdifferentiation of myofibroblast is complex; once transdifferentiation is complete, the myofibroblasts are able to upregulate the expression of many fibrotic proteins, such as collagen 1.…”
Section: Tlrs In Sscmentioning
confidence: 99%